2009
DOI: 10.1088/1748-6041/4/6/065003
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and in vitro biocompatibility of titanium anodized in a phosphoric acid solution at different voltages

Abstract: The surface of commercially pure titanium was modified by anodization treatment in a phosphoric acid solution at different voltages: 100 V, 200 V and 300 V. The surface characteristics of anodic TiO2 layers and their influence on the cell response were investigated. Micrographs by scanning electron microscopy revealed that the dense and uniform oxide layer obtained at 100 V exhibits a nanostructured surface which is similar to the surface of natural tooth cementum. In contrast, porous oxide layers without nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
(72 reference statements)
2
32
0
2
Order By: Relevance
“…The crystal growth in these places was not easily obstructed by adjacent crystals, making the formation of long wire-like crystals possible there. The energy dispersive spectrometry analysis of the wire-like products showed that the [Ti]/[P] ratio was close to 1.0, which is indicative of Ti(OH)PO 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal growth in these places was not easily obstructed by adjacent crystals, making the formation of long wire-like crystals possible there. The energy dispersive spectrometry analysis of the wire-like products showed that the [Ti]/[P] ratio was close to 1.0, which is indicative of Ti(OH)PO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It has long been thought that their corrosion resistance can be further improved by any surface treatments that can thicken the surface TiO 2 film [3]. The frequently-used techniques to thicken the TiO 2 film include thermal spraying, thermal annealing and electrochemical anodization [3,4]. Among these techniques, anodization of titanium has attracted great attention because it is simple to perform and the fabricated TiO 2 films exhibit enough thickness, good adhesion and varied structures [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a and b presents the typical surface appearance of titanium anodized at a voltage exceeding the breakdown voltage. The breakdown voltage of titanium depends on the type and concentration of electrolyte [22][23][24]. For the anodization of titanium in 1 M phosphoric acid solution, the breakdown voltage is about 150 V [24].…”
Section: Adhesion Testmentioning
confidence: 99%
“…Anodic oxidation technique presents some advantages such as easily well-adhered oxide film deposited on titanium surface through an electrochemical process. Porous and roughness films can be formed by applying high voltage to produce dielectric breakdown [6][7][8][9][10][11][12]. Extensive research in titanium shows that the morphology, surface chemistry, roughness, rutile and anatase phases significantly influences the apatite-inducing ability [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%